2016
DOI: 10.1063/1.4942966
|View full text |Cite
|
Sign up to set email alerts
|

d ferromagnetism in black phosphorous oxide caused by surface P-O bonds

Abstract: The room-temperature d0 ferromagnetism in black phosphorous (BP) oxide is investigated experimentally and theoretically. Electrochemical oxidation does not alter the single-crystal structure of BP and the degree of oxidation depends on the oxidation time, thereby resulting in changeable d0 ferromagnetism caused by surface P-O bonds. First-principles calculation reveals that different surface P-O bonds have different binding energies and contributions to the ferromagnetism and the bridge and dangling oxygen ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, the typical characteristics of P-P bond can be observed at $129.9 and $130.4 eV in the XPS P2p spectra of S-P/rGO and P/rGO, 34,35 while the peaks at around 134.1 and 134.8 eV can be assigned to P-O bond (Figure 2C) owing to the surface oxidation. 36,37 Compared with the P/rGO, a pair of new peaks in S-P/rGO located at $133.1 and $133.9 eV can be fitted, which are ascribed to the newly formed P-S bond. 38 The magnified XPS P2p spectrum and the highlighted P-S bond are illustrated in Figure S4.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, the typical characteristics of P-P bond can be observed at $129.9 and $130.4 eV in the XPS P2p spectra of S-P/rGO and P/rGO, 34,35 while the peaks at around 134.1 and 134.8 eV can be assigned to P-O bond (Figure 2C) owing to the surface oxidation. 36,37 Compared with the P/rGO, a pair of new peaks in S-P/rGO located at $133.1 and $133.9 eV can be fitted, which are ascribed to the newly formed P-S bond. 38 The magnified XPS P2p spectrum and the highlighted P-S bond are illustrated in Figure S4.…”
Section: Resultsmentioning
confidence: 97%
“…Thirdly, the studies on 2D group VA heterostructures to date have mainly focused on their electronic and optical properties, while their magnetic properties have scarcely been investigated. It has recently been reported that the ferromagnetic order can be induced by phosphorene [111] and Sb [112]. In particular, robust above-room-temperature ferromagnetism in few-layer Sb can be triggered by nonmagnetic F adatoms.…”
Section: Discussionmentioning
confidence: 99%